2018
DOI: 10.1002/ecm.1338
|View full text |Cite
|
Sign up to set email alerts
|

Complex long‐term dynamics of pollinator abundance in undisturbed Mediterranean montane habitats over two decades

Abstract: Current notions of “pollinator decline” and “pollination crisis” mainly arose from studies on pollinators of economic value in anthropogenic ecosystems of mid‐latitude temperate regions. Comprehensive long‐term pollinator data from biologically diverse, undisturbed communities are needed to evaluate the actual extent of the so‐called “global pollination crisis.” This paper analyzes the long‐term dynamics of pollinator abundance in undisturbed Mediterranean montane habitats using pollinator visitation data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 130 publications
(311 reference statements)
2
91
0
Order By: Relevance
“…Another intensive study of protected fields and meadows yielded no 20-yr net decline in the abundance of insect pollinators (Herrera 2018). Another intensive study of protected fields and meadows yielded no 20-yr net decline in the abundance of insect pollinators (Herrera 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Another intensive study of protected fields and meadows yielded no 20-yr net decline in the abundance of insect pollinators (Herrera 2018). Another intensive study of protected fields and meadows yielded no 20-yr net decline in the abundance of insect pollinators (Herrera 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Correlative and experimental evidence alike has recently shown that, at local or regional scales, honeybees can have strong negative impacts on wild bee populations in both natural and anthropogenic scenarios (Shavit et al 2009, Lindström et al 2016, Torné-Noguera et al 2016, Magrach et al 2017, Ropars et al 2019, Valido et al 2019), and that the absence of honeybees in well-preserved natural areas is associated with increasing wild bee populations (Herrera 2019). Much of the direct or circumstantial evidence on the harmful effects of honeybees on wild bees originated in the Mediterranean Basin, which motivated the hypothesis formulated in this paper of a possible replacement of wild bees by honeybees in the Mediterranean running parallel to the increasing abundance of honeybees.…”
Section: Discussionmentioning
confidence: 99%
“…S1, Potts et al 2010, vanEngelsdorp and Meixner 2010). Honeybees can have strong negative impacts on wild bee populations in both natural and anthropogenic scenarios (Shavit et al 2009, Lindström et al 2016, Torné-Noguera et al 2016, Herrera 2019, Ropars et al 2019, Valido et al 2019). I thus formulated the hypothesis that, if the abundance of managed honeybees has been actually increasing in the Mediterranean Basin over the last decades, then a profound biome-wide alteration in the composition of bee pollinator assemblages could be currently underway there, involving a progressive replacement of wild bees by honeybees in flowers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after the widespread habitat destruction during World War I, it is perhaps surprising that butterflies and moths saw a reversal in fortunes, although there are exceptions (Bretherton, 1951). Whilst it is rarely recognised or cited that insects may profit as a result of environmental change (Bell et al, 2015;Herrera, 2019, Boyes et al, 2019, Macgregor et al, 2019, it adds a dimension to the question of whether insects are declining and if so at what rate, because it suggests that to answer such a question will be dependent on the species or group studied, ignoring other likely important covariates such as habitat, spatio-temporal issues, statistical methodology and sampling intensity and bias, for example (McKinney, 1999;Cardoso et al, 2019;Mupepele et al, 2019;Simmons et al, 2019;Thomas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%